Korelasi Program Jalin Kesra dengan Mutu Pendidikan Agama Islam Anak Masyarakat Sangat Miskin - Khoirul Abidin, Upik (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
This article seeks to know both a Jalin Kesra (peopleâs welfare) program and an Islamic education quality of poor children as well as a correlation of the program with the quality of Islamic religious education of the poor children in Sendang, Tulungagung. This is a field research with a quantitative paradigm and inferential statistics approach. The findings of this study are; firstly, through peopleâs welfare program that emphasizes pro-poor growth strategy, by providing livestock, it is expected that the very poor communities in Sendang, Tulungagung as the recipient of this aid can breed their animals and the results can be used to meet their needs (a more proper live and moreover for the fulfillment of the educational needs of their children). Secondly, the average education quality of the children from the very poor communities in Sendang, Tulungagung is low. Thirdly, looking at the value of rxy is 0.663 and is located between 0.60-0.799, so the correlation is classified as âstrongâ. It concludes that there is a positive correlation between the program of peopleâs welfare with the quality of Islamic education of the very poor communityâs children in Sendang, Tulungagung.